JAPON HIGHER EDUCATION SYSTEM - Rasim TÖSTEN (Fırat University, 2019)
Japan is known to draw attention to its development and rapid progress in today’s world. That education system is one of dominant factors for reaching this success is suggested. That Japanese education system is playing important roles in maintaning qualified labour force, training leader and improving technology is understood. Some assessments for the problems of postgraduate education are done within the context of comparing Turkish and Japan post graduate education system. Thus, investigating of Japan from the aspect of education and policies followed in problem solving are thought to be benefical on behalf of our country. The main purpose of this study is to draw attention to alternative higher education system by analyzing Japanese higher education system. This study is limited to therotical framework. Literarure belonging to Japanese higher education system has been scanned and reported. In this context, examining the Japanese education and higher education systems; academic structure, student acceptation, management and finance issues have been handled under the sub-title of higher education. As a result its found that Turkish and Japan post graduate education system share a lot of important problems in common and as Japan has made considerable progress for being a third generation university making structural changes in recent years with the postgraduate education system strategy; Turkish postgraduate education system now having a structural change, a new post graduate education model is suggested.